Perbedaan Pengetahuan Ibu Balita Sebelum Dan Sesudah Dilakukan Penyuluhan Tentang Status Gizi Balita Umur 1-5 Tahun di Posyandu 1 Cokromenggalan Kecamatan Ponorogo Kabupaten Ponorogo - Hariyanto Hariyanto; Delya Putri Cahyani (Jurnal Delima Harapan, 2017)
Nutrition status is a condition of the body caused by the balance between nutrientintake and the needs. The balance can be seen from growth variable, such us bodyweight, height or body length, head circumference, and arm circumference. The purposeof this research was to know the difference of mothers’ knowledge before and aftercounseling about nutritional status of children 1-5 years old in Posyandu 1Cokromenggalan, Ponorogo Regency.This type of research was pre-experimental design. The method used AnalyticalSurvey with Cross Sectional approach. The variables in this research were knowledge ofmother toddler before and after counseling about nutrition status of children 1-5 yearsold. Data collected by questionaire. The population of 47 respondents and samples of 42mothers who have under five years children using Accidental sampling technique inJanuary 2017.The result of the research showed that the knowledge of the mother beforecounseling was 25 respondents (59,5%) in the sufficient category, the knowledge ofmother after counseling was 30 respondents (71,4%) in good category. Based on theresult of paired T test, the significance level 0.000 <0,05 so H0 was rejected, it meanthere was difference knowledge of mothers’ before and after counseling about nutritionalstatus of children 1-5 years old.It is advisable to health workers to increase extension activities to under-fiveyears children mothers to increase their knowledge and insight about nutritional status oftoddlers age 1-5 years.